The Holocaust of the Roma in retributive justice - Smlsal, Jiří (Romano džaniben, 2018)
The study deals with two postwar retribution trials concerning the Holocaust of the Roma. In the first trial the former head of Lety u Písku concentration camp was charged, in the latter a Romani prisoner funcionary was prosecuted. The study attempts to compare the two retribution trials with regards to the narrative strategies and the language used by its actors. It focuses on certain aspects of the postwar politics of memory as well as on the omission of Romani experience during retribution trials
Keywords: Roma; Holocaust; retribution trials; postwar Czechoslovakia; politics of memory; concentration camps